Dibalik Model Kerja Fast Fashion: Pengaruh Inditex Terhadap Eksploitasi Buruh Garmen di Bangladesh - Mikael Witarka; Mohamad Rosyidin; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The shift in the fashion world which is increasingly popular has prompted a Spanish company, Inditex, to implement a fast fashion work model. This work model is then implemented by Inditex through investment and technology transfer to developing countries such as Bangladesh. However, this work model is prone to labor exploitation and actually creates dependence and backwardness for Bangladesh itself. This research will use Dependency Theory. The method used in this study is a qualitative research with data collection techniques used is the literature study method. So this study tries to prove that the work model that Inditex runs actually creates state dependence and underdevelopment of garment workers in Bangladesh. The result of this research is that Inditex actually maintains Bangladesh's dependence on the fashion company, Inditex's actions are full of injustice but on the other hand Bangladesh needs foreign capital assistance from Inditex to help thecountry's economy.